1993
DOI: 10.1002/jcp.1041570125
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐integrin antibodies induce type IV collagenase expression in keratinocytes

Abstract: During wound healing, pericellular proteolysis is thought to be essential for the detachment of keratinocytes from basement membrane and in their migration into the wound bed. We have characterized integrin-type cell adhesion/migration receptors in human mucosal keratinocytes and examined their function in the regulation of type IV collagenase gene expression. Two major integrins of the beta 1 class, alpha 2 beta 1 and alpha 3 beta 1, were found to function as collagen and fibronectin receptors, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 70 publications
3
36
1
Order By: Relevance
“…Also, MAb 13, directed against ␤1 integrin, 23 induced pro-MMP-9 expression, possibly by acting as the natural ligand on its receptor, in agreement with studies of keratinocytes showing pro-MMP-9 induction by the same antibody. 28 Since collagen I is a ubiquitous component of the prostate and bone stroma, a major site of PC metastasis, our data suggest that specific interactions of PC cells with the collagenous ECM may facilitate matrix breakdown and eventually tumor invasion through the induction of proteolytic enzymes in tumor cells. We speculate that collagen I in bone, whether as a part of the ECM or in soluble form, may stimulate the expression of MMP-9 by PC cells, leading to increased bone turnover and release of collagen I, resulting in a vicious cycle of bone matrix degradation and tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Also, MAb 13, directed against ␤1 integrin, 23 induced pro-MMP-9 expression, possibly by acting as the natural ligand on its receptor, in agreement with studies of keratinocytes showing pro-MMP-9 induction by the same antibody. 28 Since collagen I is a ubiquitous component of the prostate and bone stroma, a major site of PC metastasis, our data suggest that specific interactions of PC cells with the collagenous ECM may facilitate matrix breakdown and eventually tumor invasion through the induction of proteolytic enzymes in tumor cells. We speculate that collagen I in bone, whether as a part of the ECM or in soluble form, may stimulate the expression of MMP-9 by PC cells, leading to increased bone turnover and release of collagen I, resulting in a vicious cycle of bone matrix degradation and tumor cell proliferation.…”
Section: Discussionmentioning
confidence: 81%
“…7c), suggesting that binding of the MAb to its receptor triggers a signaling pathway in PC cells similar to that elicited by collagen I and leading to pro-MMP-9 secretion. 28 As controls, anti-␣5 (MAb 16) (Fig. 7d) and non-immune IgG (Fig.…”
Section: Effect Of Anti-integrin Antibodies On Pro-mmp-9 Expressionmentioning
confidence: 99%
“…a3b1 integrin was shown to participate in phagocytosis of extracellular matrix (Coopman et al, 1996). a2b1, a3b1, a4b1, and a5b1 integrin were found to be involved in the regulation of matrix metalloprotease expression (Larjava et al, 1993;Huhtala et al, 1995;Riikonen et al, 1995). In addition, activation of a6b1 integrin increased invasiveness of LOX human melanoma cells correlating with a 2 ± 3-fold elevation of extracellular matrix degradation and invadopodial activity (Nakahra et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It was initially observed that antibodies blocking α 5 β 1 integrin-mediated adhesion induced MMP expression in fibroblasts (Werb et al, 1989). Later studies revealed that integrin-mediated signals are general regulators of MMP expression, as α 2 β 1 integrin regulates MMP-1 expression (Riikonen et al, 1995;Dumin et al, 2001), antibodies to α 3 β 1 integrin-tetraspanin complexes induce MMP-2 expression (Sugiura and Berditchevski, 1999), and α M β 2 and α 3 β 1 integrin ligation stimulates MMP-9 expression (Wize et al, 1998;Larjava et al, 1993). The effects on MMP expression are very specific.…”
Section: Expression and Secretion Of Gelatinases And Other Mmpsmentioning
confidence: 99%